All-creation and all-annihilation time-dependent PT -symmetric bosonic Hamiltonians: An infinite squeezing degree at a finite time - De Ponte, M. A. [UNESP]; Luiz, F. S.; Duarte, O. S.; Moussa, M. H.Y. (American Physical Society (APS), 2019)
Here we introduce the all-creation and all-annihilation time-dependent (TD) PT-symmetric bosonic Hamiltonians, which in the interaction picture are described only by creation or annihilation operators. These Hamiltonians are defined from the most general TD PT-symmetric quadratic bosonic Hamiltonian, describing a cavity mode under linear and parametric amplifications. After presenting a general ansatz for the derivation of the TD Dyson map and metric operators, we solve the Schrödinger equations for both the PT-symmetric Hamiltonian and its Hermitian counterpart. We then compute analytically the squeezing degree coming from the all-annihilation Hamiltonian and compare the result with that coming from an ordinary Hermitian Hamiltonian, showing a crucial result for interferometric procedures: instead of the asymptotic divergence of the squeezing degree that takes place for a Hermitian parametric pumping, the all-annihilation amplification leads to a divergence of that quantity at a finite controllable time.